Cities with forking paths? Agglomeration economies in New Zealand 1976-2018 - Stuart Donovan; Thomas de Graaff; Arthur L. Grimes; Henri L. F. de Groot; David Christopher Maré (Tinbergen Institute, 2021)
We consider whether external urban economic advantages (agglomeration economies) vary with time and space using a simple economic model and detailed micro-data on 134 locations in New Zealand for the period 1976-2018. We find subtle temporal variation, with estimates peaking in 1991 and then falling over the next 15-years by approximately 1%. Since 2006, however, estimates have remained broadly stable. Our results reveal more significant spatial variation: Large cities offer net benefits in production, but not in consumption, whereas small locations close to large cities ("satellites") experience agglomeration economies that are stronger than average.
Keywords: R11; R23; R30; 330; agglomeration economies; cities; productivity; consumption; New Zealand